Faktor – Faktor yang Mempengaruhi Kejadian Diastasis Recti Abdominis pada Wanita Post Partum - Gusti Ayu Made Intan Rama Apsari; Ni Luh Nopi Andayani; Made Widnyana (Syntax Corporation Indonesia, 2024)
Pregnancy and childbirth are cycles experienced by most women. There are many things that happen to a woman's body during pregnancy and postpartum, one of which is the separation of the linea alba in the abdominal muscles or known as Diastasis Recti Abdominis. Diastasis Recti Abdominis or DRA is an event where there is separation of the abdominal muscles. Post partum is the period or time when the reproductive organs experience recovery or return to their original state as before pregnancy. The purpose of this study was to determine the factors that can influence the incidence of Diastasis Recti Abdominis in postpartum women. The method used in this study is a literature review study using secondary data in the form of a review of research journals related to factors that affect the incidence of diastasis recti abdominis in postpartum women. Literature is obtained by accessing the pages of Google Schoolar, and PubMed. Results: There are several factors that can influence the incidence of Diastasis Recti Abdominis, namely gestational age (30%), overweight or obesity (60%), and diabetes (30%). Conclusion: Based on some of the literature found, it can be concluded that gestational age, overweight or obesity, and diabetes are factors that can influence the incidence of Diastasis Recti Abdominis in postpartum women.